-6v+30=8(v+9)

Simple and best practice solution for -6v+30=8(v+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6v+30=8(v+9) equation:


Simplifying
-6v + 30 = 8(v + 9)

Reorder the terms:
30 + -6v = 8(v + 9)

Reorder the terms:
30 + -6v = 8(9 + v)
30 + -6v = (9 * 8 + v * 8)
30 + -6v = (72 + 8v)

Solving
30 + -6v = 72 + 8v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-8v' to each side of the equation.
30 + -6v + -8v = 72 + 8v + -8v

Combine like terms: -6v + -8v = -14v
30 + -14v = 72 + 8v + -8v

Combine like terms: 8v + -8v = 0
30 + -14v = 72 + 0
30 + -14v = 72

Add '-30' to each side of the equation.
30 + -30 + -14v = 72 + -30

Combine like terms: 30 + -30 = 0
0 + -14v = 72 + -30
-14v = 72 + -30

Combine like terms: 72 + -30 = 42
-14v = 42

Divide each side by '-14'.
v = -3

Simplifying
v = -3

See similar equations:

| 22=6(u+5)-8u | | 7n^2=46n+21 | | 11r=-88 | | 5(3x+2)=10x+5 | | 4t(t-5)-2t(2t+2)+108=3t(2t-5)-t(8t-3) | | -1/4=1/5u-2/3 | | ax+4=40 | | -6u+4(u-6)=-16 | | (3x^(2/3))^-1 | | ln(2x+1)=2.25 | | -3(5s-4)-12=-3(9s+1)-5 | | -3(-3x-4)=4(x+2)-2(x+8)-1 | | 3(x-2)/4=-9 | | 3(-6b+2-8b)=-12b+36 | | 14x-7=8x+41 | | 2/3w-7/5=-5/4 | | 8k^2+72k+60=-4 | | 6m-1=m+20 | | V=100cm | | 4x(4-x)=5x | | 0.03(x+5)=0.9 | | 1/2=(x/4)^1/4 | | 4x+50=20 | | 2x+8+6= | | .02r+0.75=0.5r | | -9(x+8)=5x+26 | | 1800x+1400y= | | log[2](x)=0.03*x^2 | | 7x+x+x+5=5x+4x | | 0.3x-8=0.5x+10 | | 7-d+14=0 | | 440x+40y= |

Equations solver categories